2017
DOI: 10.1007/s00467-017-3597-4
|View full text |Cite
|
Sign up to set email alerts
|

Vasculitis update: pathogenesis and biomarkers

Abstract: Better understanding of the pathogenesis and treatment of primary systemic vasculitides (PSV) has led to the development of many potentially clinically relevant biomarkers. Genome-wide association studies have highlighted that MHC class II polymorphisms may influence the development of particular anti-neutrophil cytoplasmic antibody (ANCA) serotypes, but not the clinical phenotype of ANCA-associated vasculitis (AAV). Although ANCAs are overall poor biomarkers of disease activity, they may be useful for the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 110 publications
(160 reference statements)
0
33
0
3
Order By: Relevance
“… 102 In addition, deficiency of adenosine deaminase type 2 (DADA2), an autosomal recessive disease, representing with lacunar stroke, vasculitic peripheral neuropathy, livedo racemosa and systemic inflammation is a possible differential diagnosis to PACNS with manifestation in early childhood. 103 …”
Section: Differential Diagnosismentioning
confidence: 99%
“… 102 In addition, deficiency of adenosine deaminase type 2 (DADA2), an autosomal recessive disease, representing with lacunar stroke, vasculitic peripheral neuropathy, livedo racemosa and systemic inflammation is a possible differential diagnosis to PACNS with manifestation in early childhood. 103 …”
Section: Differential Diagnosismentioning
confidence: 99%
“…Moreover, the measurement of VWF may be a valuable biomarker because a decrease in VWF levels in serum seems to indicate improvement of cPACNS disease activity (16). Von Willebrand factor antigen levels increase in serum in response to endothelial injury or activation; therefore, monitoring of VWF levels may reflect disease activity in many vasculitis (56,57). However, another study in pediatric PACNS found VWF levels to be a poor discriminator of disease activity, and a study of VWF in adults with antineutrophil cytoplasmic antibody-associated vasculitis observed the persistence of high levels of VWF when patients were considered to be in clinical remission (58,59).…”
Section: Coagulation Diagnosticsmentioning
confidence: 99%
“…Dies könnte sich jedoch durch internationale Kooperation und die Verwendung moderner Technologien in der nahen Zukunft ändern. Die Identifikation von Mutationen im für die Adenosin Deaminase 2 kodierende CECR1 Gen führte zur Beschreibung des Erkrankungsbildes DADA2 [10,31,32]. Ein Teil der Patienten mit vermuteter PACNS weist krankheitsauslösende Mutationen in CECR1 auf, was zur Reklassifikation dieser Fälle von PACNS zu DADA2 führt [10,31,32].…”
Section: Aktuelle Herausforderungen Und Chancenunclassified
“…Die Identifikation von Mutationen im für die Adenosin Deaminase 2 kodierende CECR1 Gen führte zur Beschreibung des Erkrankungsbildes DADA2 [10,31,32]. Ein Teil der Patienten mit vermuteter PACNS weist krankheitsauslösende Mutationen in CECR1 auf, was zur Reklassifikation dieser Fälle von PACNS zu DADA2 führt [10,31,32]. Patienten mit DADA2 können erfolgreich mit TNF Blo- ckade therapiert werden [33].…”
Section: Aktuelle Herausforderungen Und Chancenunclassified